2017
DOI: 10.1053/j.gastro.2016.09.009
|View full text |Cite|
|
Sign up to set email alerts
|

Eradication of Hepatitis C Virus Infection in Patients With Cirrhosis Reduces Risk of Liver and Non-Liver Complications

Abstract: We confirmed a reduction in critical events, liver-related or not, in a prospective study of patients with HCV infection and compensated cirrhosis included in the CirVir cohort who achieved an SVR. We found an SVR to reduce overall mortality and risk of death from liver-related and non-liver-related causes. A longer follow-up evaluation is required to accurately describe and assess specific risk factors for complications in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
403
3
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(445 citation statements)
references
References 39 publications
22
403
3
17
Order By: Relevance
“…The findings were in line with other studies that evaluated the HCC risk of patients with an interferon-based regimen (3)(4)(5). Several prospective studies have evaluated the subsequent risk of HCC among patients who underwent DAA treatment (6)(7)(8). However, DAAs are recently developed regimens; therefore, the period of follow-up in studies of DAA-treated patients were relatively short compared with studies that analysed patients treated with interferon-based regimens.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The findings were in line with other studies that evaluated the HCC risk of patients with an interferon-based regimen (3)(4)(5). Several prospective studies have evaluated the subsequent risk of HCC among patients who underwent DAA treatment (6)(7)(8). However, DAAs are recently developed regimens; therefore, the period of follow-up in studies of DAA-treated patients were relatively short compared with studies that analysed patients treated with interferon-based regimens.…”
supporting
confidence: 84%
“…The large study population and the existence of comprehensive electronic medical records were suitable for the study of HCV treatment outcomes in a realworld setting. Although 40% of patients already had liver cirrhosis, compared with other prospective studies aimed to estimate HCC risks among patients treated in tertiary centres (6)(7)(8), the veterans included in this study were relatively healthy. However, at least 96% of participants were male, which limited the study's generalizability.…”
mentioning
confidence: 99%
“…Data from these two studies could not, however, be pooled together because of the differences in the comparison groups (SVR vs non-SVR,17 and interferon-based treatment vs no treatment18). In the study of Nahon et al ,17 a significant effect of SVR achievement on the incidence of major adverse cardiovascular events was reported (OR 0.37 (95% CI 0.59 to 0.84)) (online supplementary appendix 10B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FL reportedly induces oxidative DNA damage in cancer-related genes, which can also be a risk for HCC [35] . Recent reports have also indicated that CHC patients with metabolic features, such as DM, HL, and obesity after IFN therapy shows a higher incidence of HCC emergence than those without metabolic features and that these findings were with respect to both SVR and non-SVR patients [36] . As IFN-free DAA treatment is widely applicable in patients under high risk of HCC, patients with FL, high FIB-4 index, and low ALB level should be carefully monitored for HCC emergence even after the achievement of SVR.…”
Section: Discussionmentioning
confidence: 96%